Strategi Komunikasi Pemasaran UMKM (Studi Kasus Produk Makanan Mille Crepes Palace di Kutabumi Pasarkemis) - Fazrin, Erin; Romadoni, Suci; Noris, M Caesar; Yuliarti, Herlina (Al-DYAS, 2024)
This study aims to analyze and develop an effective marketing communication strategy for MSMEs (Micro, Small and Medium Enterprises) with a case study on Mille Creeps food products in Kotabumi Pasarkemis. Mille Creeps is one of the SMEs engaged in the food industry in the region. This research was conducted with the aim of increasing understanding of effective marketing communication strategies to help MSMEs such as Mille Creeps in facing existing marketing challenges. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with the owners and managers of Mille Creeps, direct observation, and analysis of documents related to the marketing strategy carried out by these MSMEs. The collected data will be analyzed using qualitative analysis techniques, by identifying the factors that influence MSME marketing communications and formulating appropriate strategies. The results of this study are expected to provide a better understanding of the challenges faced by MSMEs in terms of marketing and offer communication strategies that can assist MSMEs in increasing the success of marketing their products. It is hoped that the results of this study can contribute to other MSME owners and become a reference for further research in this field.